Evaluating the Effectiveness of Incentives to Improve HIV Prevention Outcomes for Young Females in Eswatini : Sitakhela Likusasa Impact Evaluation Protocol and Baseline Results - Gorgens, Marelize; Longosz, Andrew F; Ketende, Sosthenes; Nkambule, Muziwethu; Dlamini, Tengetile; Mabuza, Mbuso; Sikwibele, Kelvin; Tsododo, Vimbai; Dlamini, Mthokozisi; Dennis-Langa, Futhie; Heard, Wendy; Low, Andrea; et al. (BMC/Springer Nature, 2022)
Eswatini continues to have the highest prevalence of HIV in the world, and one of the highest HIV incidences among adult populations (aged 15–49). This analysis reports on both key elements of study design/protocol and baseline results from an impact evaluation of an intervention incentivizing (i) initiation, enrolment, attendance or completion of some form of education, and (ii) lower risk sexual behavior.